DETERMINATION OF PORT FACILITIES AND CONTAINER FLOW GROWTH TOWARD THE DEVELOPMENT OF MAKASSAR PORT, INDONESIA - Prasadja Ricardianto; Muhammad Thamrin; Yosi Pahala (ABNUS Publisher, 2022)
The aim of this research is to know the determination of port facilities and container flow growth mediated by spatial regulation toward the development of Makassar Port in the South Sulawesi province. The main problem of Makassar Port is the capacity of wharf and terminal container yard Hatta which has been almost in the optimal condition due to the limited port land which is in the center of Makassar City and has not been integrated with the transportation modes in the port area. This research uses the path analysis, with sample as many as 133 persons from Makassar Main Port Authority Office, Local Government of Makassar City, Pelabuhan Indonesia IV, and Makassar Container Terminal as well as Port Directorate of Directorate General of Sea Transportation. The result of this research states that there is no determination of Spatial Regulation which neither strengthens nor weakens the relationship between Port Facilities and Port Development. It is expected that the preparation of Regional Spatial Plan pays attention to the need for space to build port facilities by providing a space for port development. The unavailability of space will force the optimization of port facilities in the existing port and become a negative determination to the need for port development. It needs coordination with the Local Government so that the spatial regulation supports the development of Makassar Port.